Financing Industrial Innovation: Empirical Research on the Impact of Sectoral Bank Credit on Business Development in Cambodia - Pisith Hok; Sarom Mok; Bora Khath; Tharith Pin (International Journal of Educational Innovation and Research, 2026)
This empirical study examines the linkage between bank credit and innovation of sectors as determinants of economic growth in Cambodia for the period from 2009 to 2023. Quantitative approach and secondary data in the form of time series data will be used in the study. The data is sourced from National Bank of Cambodia and International Monetary Fund, and the analysis will involve simple and multiple regressions. Results indicate that while bank credit expansion (reaching 175.01% of GDP by 2023) acts as a powerful force for economic growth, its impact is highly uneven across industries. The findings show that the credit that was designed to aid real estate, agriculture, and media and telecommunications is the one that has made positive impacts on growth, while credit aimed at mining, utility, and hospitality industries has caused negative impacts. This means that current innovation in the industry has been centered on developments in urban settings and information technology, and not capital-intensive industries. According to the findings, for sustainable growth, the government should move from expanding credit to strategically allocating credit in the productive and innovative sectors. This paper addresses the finance-growth literature in developing countries and offers a framework for distributing credit strategically.